The Potential Impacts of Climate Change on Human Health and the Need for Health Education in Kenya - Agwata, Jones (Joypet Sevices & Printers Ltd, 2007)
Human health is dependent on a good and clean environment and many of the factors that lead to a deteriorated environment also lead to poor health. Pollution of the atmosphere, lack of sufficient and! or polluted water supplies and other forms of environmental degradation, for instance, present serious dangers to human health and well being and contribute to the spread of various diseases. Many of these factors tend to be exacerbated through climate change while increased incidences of climate hazards such as droughts and floods lead to higher human health risks from a variety of causes. In this paper the potential effects of climate change on human health are highlighted and the need for appropriate research and training needs with a view to establishing appropriate measures and mechanisms for adapting and/or responding to the various climate change-human health related effects proposed.